1998
DOI: 10.1046/j.1365-2567.1998.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of GM1 binding in the mucosal immunogenicity and adjuvant activity of the Escherichia coli heat‐labile enterotoxin and its B subunit

Abstract: SUMMARYEscherichia coli (E. coli ) heat-labile toxin (LT ) is a potent mucosal immunogen and immunoadjuvant towards co-administered antigens. LT is composed of one copy of the A subunit, which has ADP-ribosylation activity, and a homopentamer of B subunits, which has affinity for the toxin receptor, the ganglioside G M1 . Both the ADP-ribosylation activity of LTA and G M1 binding of LTB have been proposed to be involved in immune stimulation. We investigated the roles of these activities in the immunogenicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
54
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 31 publications
4
54
0
Order By: Relevance
“…[38][39][40] To evaluate the receptor-binding ability of CTB-HC and CTB-C2 fusion proteins produced in tobacco chloroplasts, GM1-binding ELISA was performed. As observed in Figure 2E, CTB-HC and CTB-C2 fusion protein extracts along with purified CTB protein showed strong binding affinity to GM1.…”
Section: Pentamer Assembly Of Ctb-hc and Ctb-c2 In Transgenic Chloropmentioning
confidence: 99%
“…[38][39][40] To evaluate the receptor-binding ability of CTB-HC and CTB-C2 fusion proteins produced in tobacco chloroplasts, GM1-binding ELISA was performed. As observed in Figure 2E, CTB-HC and CTB-C2 fusion protein extracts along with purified CTB protein showed strong binding affinity to GM1.…”
Section: Pentamer Assembly Of Ctb-hc and Ctb-c2 In Transgenic Chloropmentioning
confidence: 99%
“…However, the results obtained with LT-B and CT-B alone as mucosal adjuvants are highly inconsistent. Studies have shown that neither LT-B nor CT-B enhance immune responses to mucosal co-administered protein antigens when given orally [165,231], whereas some other reports have suggested that LT-B and CT-B could display mucosal adjuvant activity when intranasally administered (large doses) in combination with proteins (large doses) [46,47,52,165]. Antibody responses can be observed when LT-B or CT-B are directly conjugated to the antigen itself [165] and are given either orally or intranasally (Tab.…”
Section: Ct-b and Lt-bmentioning
confidence: 99%
“…Application to the nasal mucosal environment in mice resulted in specific translocation of exotoxin (or exotoxin subunits) and coadministered Ags to the CNS, raising concerns about undesirable neurotoxicity (18,19). To reduce toxicity, modified exotoxins are described in which the A subunit is mutated or deleted to reduce or eliminate ribosylation activity (20,21). However, these formulations may still retain toxicity due to residual ribosylation activity, or there is an undesirable loss of adjuvanticity (15,22).…”
mentioning
confidence: 99%